Analisis Produktivitas Kerja Karyawan BPN Kabupaten Brebes Tahun 2023 - Aditya Pamungkas; Efriyani Sumastuti; Ratih Hesty Utami Puspitasari (Pusat Riset dan Inovasi Nasional, 2024)
Analysis of the work productivity of Brebes Regency BPN employees in 2023. This research is motivated by several things related to the work productivity of Brebes Regency BPN employees, namely: 1) some employees experience difficulties in carrying out their duties serving the community; 2) some employees experience a decrease in work productivity; 3) several employees have complained about carrying out their duties to serve the community; and 4) some employees do not dare to take the risk of dealing with the problem of managing residents' land in Brebes Regency. The aim of this research is to determine the effect of compensation, work discipline, work motivation, service quality and physical work environment on the productivity of Brebes Regency BPN employees in 2023. The research method uses quantitative methods with a survey research design. Data collection techniques use observation, interviews and documentation. Test data requirements using: validity test, reliability test, normality test, multicollinearity test, and heteroscedasticity test. Statistical hypothesis testing uses multiple linear regression with the F test and t test. The data analysis technique uses descriptive statistics. The results of the research show that there is a simultaneous influence of compensation, work discipline, motivation, service quality, and physical work environment on the work productivity of BPN (National Land Agency) Brebes Regency employees in 2023. Meanwhile, the service quality variable does not have a significant influence on employee work productivity BPN (National Land Agency) Brebes Regency in 2023.